National VET Research Report Austria - Tritscher-Archan, Sabine [Herausgeber]; Brandstetter, Genoveva [Mitarbeiter]; Fingerlos, Astrid [Mitarbeiter]; Luomi-Messerer, Karin [Mitarbeiter]; Prokopp, Monika [Mitarbeiter]; Lassnigg, Lorenz [Mitarbeiter]; Vogtenhuber, Stefan [Mitarbeiter] (Institut für Bildungsforschung der Wirtschaft, 2009)
This report is part of a series of country reports on national research priorities in the field of VET in the EU member states, Norway and Iceland ('National VET Research Report'). It "provides an overview of the state of research in the following four areas of vocational education and training (VET): (a) the benefits of VET; (b) VET and employment-related mobility and migration; (c) governance of the VET system; (d) labour market groups at risk. Each chapter first of all analyses relevant research questions and challenges in Austria before presenting and discussing the main findings of available research projects. In the final synopsis, conclusions are drawn from research findings and implications for further research work demonstrated." (Hrsg., BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; S 1 Stufen der Berufsbildung; I 2.2.1 Westeuropa; Berufsbildungsforschung; Berufsbildung; Kosten-Nutzen-Relation; Berufliche Mobilität; Benachteiligter; Migrant; Bildungssteuerung; Arbeitsmarktrisiko; Österreich